Electrophysiological characterization of activation state-dependent Cav2 channel antagonist TROX-1 in spinal nerve injured rats. (25th June 2015) - Patel, R.; Rutten, K.; Valdor, M.; Schiene, K.; Wigge, S.; Schunk, S.; Damann, N.; Christoph, T.; Dickenson, A.H.
Highlights: TROX-1 exhibits activation state-dependent inhibition of Cav 2.2 in vitro . TROX-1 selectively attenuates neuronal responses to mechanical stimulation. Anti-nociceptive effect of TROX-1 dependent on pathophysiological state. Abstract: Prialt, a synthetic version of Cav 2.2 antagonist ω-conotoxin MVIIA derived from Conus magus, is the first clinically approved voltage-gated calcium channel blocker for refractory chronic pain. However, due to the narrow therapeutic window and considerable side effects associated with systemic dosing, Prialt is only administered intrathecally. N-triazole oxindole (TROX-1) is a novel use-dependent and activation state-selective small-molecule inhibitor of Cav 2.1, 2.2 and 2.3 calcium channels designed to overcome the limitations of Prialt. We have examined the neurophysiological and behavioral effects of blocking calcium channels with TROX-1. In vitro, TROX-1, in contrast to state-independent antagonist Prialt, preferentially inhibits Cav 2.2 currents in rat dorsal root ganglia (DRG) neurons under depolarized conditions. In vivo electrophysiology was performed to record from deep dorsal horn lamina V/VI wide dynamic range neurons in non-sentient spinal nerve-ligated (SNL) and sham-operated rats. In SNL rats, spinal neurons exhibited reduced responses to innocuous and noxious punctate mechanical stimulation of the receptive field following subcutaneous administration of TROX-1, an effect that was absent in sham-operated animals. No effect was observed on neuronal responses evoked by dynamic brushing, heat or cold stimulation in SNL or sham rats. The wind-up response of spinal neurons following repeated electrical stimulation of the receptive field was also unaffected. Spinally applied TROX-1 dose dependently inhibited mechanically evoked neuronal responses in SNL but not sham-operated rats, consistent with behavioral observations. This study confirms the pathological state-dependent actions of TROX-1 through a likely spinal mechanism and reveals a modality selective change in calcium channel function following nerve injury.